1983
DOI: 10.1128/jb.153.1.340-344.1983
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive uptake and degradation of fatty acids by Yersinia pestis

Abstract: Yersinia pestis was found to utilize palmitic acid as a primary carbon and energy source. No inhibition of growth by palmitic acid was observed. Comparison of palmitic acid uptake by cells pregrown either with or without palmitic acid demonstrated that fatty acid uptake was constitutive. High basal levels of two enzymes of n-oxidation, P-hydroxyacyl-coenzyme A dehydrogenase and thiolase, MATERIALS AND METHODS Bacteria and growth conditions. Y. pestis EV76 (Pgm-Vwa+ Fra+ Pst+ Cal') and a derivative of EV76 whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…For each strain, a 9-ml bacterial preculture at the late exponential growth phase (incubation at 28°C for 24 h with no shaking) was used to inoculate a 50-ml liquid growth medium with a concentration of 5 ϫ 10 7 CFU/ml calculated from the optical density at 600 nm. These cultures were incubated for a further 24 h at 28°C with no shaking, allowing the population to reach the early stationary growth phase where the fatty acid composition is rather stable (14,30,41). It was important to use the same growth temperature of 28°C to be able to compare the fatty acids patterns of Y. pestis with those of other Yersinia species computerized in our data base.…”
Section: Bacterial Strains a Total Of 29 Strains Of Y Pestis From Tmentioning
confidence: 99%
“…For each strain, a 9-ml bacterial preculture at the late exponential growth phase (incubation at 28°C for 24 h with no shaking) was used to inoculate a 50-ml liquid growth medium with a concentration of 5 ϫ 10 7 CFU/ml calculated from the optical density at 600 nm. These cultures were incubated for a further 24 h at 28°C with no shaking, allowing the population to reach the early stationary growth phase where the fatty acid composition is rather stable (14,30,41). It was important to use the same growth temperature of 28°C to be able to compare the fatty acids patterns of Y. pestis with those of other Yersinia species computerized in our data base.…”
Section: Bacterial Strains a Total Of 29 Strains Of Y Pestis From Tmentioning
confidence: 99%
“…It will become apparent in this review that the link between virulence and metabolism is so important in many pathogens that we are probably only seeing the tip of the iceberg. Using the example of the type three secretion system (T3SS), a prototypic virulence determinant of many Gram-negatives, we will show in particular that not only metabolism controls and underpins production and functioning of virulence factors but also that, conversely, virulence factors can modulate metabolic functions of pathogens in a coordinate way, as for example, in Yersinia (Moncla et al, 1983 ; Du et al, 2009 ; Schmid et al, 2009 ) or pave the way for novel metabolic options as in Salmonella (Winter et al, 2010 ) and Pseudomonas (Dacheux et al, 2001b ). The following criteria served as indicators to identify similar phenomena in other pathogens: (i) Can it be assumed or is it known that deletion of a T3SS component results in changes of metabolism?…”
Section: Introductionmentioning
confidence: 99%
“…The cross-talk between virulence functions and metabolism in Y. pestis is presumably even more complicated. Moncla et al ( 1983 ) demonstrated constitutive uptake and degradation of fatty acids in Y. pestis via β–oxidation and the glyoxylate shunt. Intriguingly, fatty acid uptake was found to depend on the T3SS-encoding plasmid pCD1 as well as on the small virulence plasmid encoding the plasminogen activator (Pla) and pesticin (Pst).…”
Section: Introductionmentioning
confidence: 99%
“…There were many fatty acids metabolites in the present dataset, where deoxycholate, oleic acid, palmitic acid, cholic acid, arachidonic acid, stearic acid and linoleic acid were observed at early timepoints whereas taurodeoxycholic acid, cholic acid, taurocholic acid and glycocholic acid were observed at late time points. Y. pestis is known to utilize palmitic acid as a carbon and energy source (Moncla et al 1983 ) and has enzymes for fatty acid degradation. We studied interaction networks among differentially expressed metabolites, which reveals the interactions between diseases and functions.…”
Section: Resultsmentioning
confidence: 99%